Parents’ knowledge, attitudes, and practices regarding child sexual abuse prevention among parents of primary school children - Suni Hariati; Almaidah; Wa Ode Nur Isnah Sabriyati; Fany Anggriany Ramadhana (Pediomaternal Nursing Journal, 2026)
Introduction: The parents' role is important in giving education about child sexual abuse prevention. Objective: This study aimed to assess the parents' knowledge, attitudes, and practices regarding Child Sexual Abuse (CSA) prevention among primary school children in Makassar City, Indonesia. Methods: A descriptive cross-sectional study was conducted among 404 parents from five primary schools in Makassar. Participants were anonymously selected using a convenience sampling technique. The inclusion criteria required that parents could use and access the internet and were able to read and understand Indonesian. The dependent variables were the knowledge, attitude, and practice, and the independent variables were parents' role, employment status, educational background, economic status, number of children, and victim of sexual violence. The KAP questionnaire was made in Google Forms and distributed to the sample via social media. The independent t-test and one-way ANOVA were used to analyze the data. Results: The mean score for CSA prevention knowledge was 7.03 ± 1.56 (range 0–10). Parental attitudes for CSA prevention showed a mean score of 4.36 ± .88 (range 0–5). The mean score for CSA prevention practices was 5.05 ± 1.60 (range 0–7). The parents' knowledge was associated with parents' role, educational background, number of children, and economic status (P-value<.005). The attitude was associated with the number of children and economic status (P-value<.005). The practice was associated with parents' roles and the number of children. Conclusion: The findings indicate moderate levels of parental knowledge, attitudes, and practices toward CSA prevention, influenced by key sociodemographic factors. These results underscore the importance of targeted parent education and strengthened school-based CSA prevention programs to improve preventive practices and child protection. Keywords: attitude; child sexual abuse; knowledge; parents; practice; primary school children